Towards coaching leadership : a study of leadership style transformation in the city of Pudasjärvi - Kolmonen, Mira (2022)
From the perspectives of Pudasjärvi's managers and employees, this master's thesis focuses on the effectiveness of coaching leadership training in management practices and the work atmosphere conducted by the University of Lapland's Training and Development Unit.